NOVEL BURUNG-BURUNG MANYAR KARYA Y.B. MANGUNWIJAYA SEBAGAI MATERI PEMBELAJARAN SASTRA: KONFLIK BATIN DAN NILAI PENDIDIKAN KARAKTER - Mage Nugroho; Suyitno Suyitno; Raheni Suhita (Universitas Sebelas Maret, 2019)
The purpose of this research is to describe; (1) inner conflict experienced by the main character in the novel Burung-Burung Manyar by Y.B. Mangunwijaya; (2) the values of character education in the novel Burung-Burung Manyar by Y.B. Mangunwijaya; and (3) the relevance of the novel Burung-Burung Manyar by Y.B. Mangunwijaya in the learning of literary appreciation in senior high school.This research applied descriptive qualitative method with the approach of literature psychology. The assessment of inner conflict was done with the psychoanalysis theory by Sigmund Freud. The data of this research were collected from the quotes in the novel Burung-Burung Manyar by Y.B. Mangunwijaya and the information from teachers. The research subjects taking was done with purposive sampling technique. The technique of data collection for this research is content analysis and interview. The validity test used triangulation of data sources and triangulation method. The flow technique is applied to analyze the data.This research reveals that there are id, ego, and superego that affect character personality. The imbalance among id, ego and superego cause inner conflict. The values of character education appear in the novel are religious, honest, tolerance, discipline, independent, curiosity, national spirit, patriotism, acknowledge achievement, friendly/communicative, social care and responsible. This novel is relevant to the instructional purpose that must be achieved from the aspect of content, presentation, language, and graphic.